Permeability behaviour of polyurethane polymer-reinforced granular material with and without clogging - Tao, Xiaosan; Gao, Zhibing (Frontiers in Physics, 2024)
Polyurethane polymer-reinforced granular material (PPGM) can be used for ground improvement due to its high strength and drainage capacity. However, in engineering practice, clogging may occur that influence the permeability of PPGM. This study makes a laboratory assessment of the permeability of PPGM with and without clogging. It is found that the permeability coefficient of clean PPGM decreases as the content of polyurethane polymer increases, due to the reduction of its porosity and pore constriction size. To account this effect, a modified constriction size formula of PPGM is proposed. With the increase of the extent of clogging, the permeability coefficient of clogged PPGM decreases due to its decrease in the constriction size. A monotonic increase of the permeability coefficient of the mean constriction size of PPGM is found.